PECULIARITIES OF THE DUAL EDUCATION IN GERMANY AS AN IMPORTANT ELEMENT OF PROFESSIONAL TRAINING - Плахотнік, Ольга; Стражнікова, Інна; Кондратюк, Алла (Київський національний університет імені Тараса Шевченка, 2022)
The need to reform the higher education system both in European countries and in Ukraine has led to the need to study the leading experience of educational practices of higher education institutions. German education is considered to be one of the best examples of high-quality modern education the practice of which is followed by the whole world.The development of german education is characterized by the transition to a dual system of education which has been successfully used in the country for more than twenty years. And, accordingly, as a result, Germany has shown high results and professional achievements of students as well as one of the lowest levels of youth unemployment. Moreover, the focus on german education is growing due to the successful combination of learning, practice and support for young people in personal and family development. Therefore, the study of Germany's best practices in the field of dual education is an important element in improving the system of Ukrainian and European education.Comparing the systems of dual and traditional learning, we tend to claim that the benefits of dual learning are obvious: 1) learning is as close as it is possible to the demands of production; 2) high employment rate; 3) increasing the diversity of educational programs; 4) more diverse professional development of the student; 5) stimulating business in investing in vocational education; 6) the implementation of scientific research is facilitated by the possibility of using modern production equipment directly in production itself; 7) there is an opportunity to influence the personality of the specialist as well as the formation of the necessary qualities of the employee in the model of the dual system of training; 8) as a technology, the dual system of training increases the motivation and need to obtain the knowledge necessary for professional activities due to the fact that the quality of acquired knowledge will allow to perform highquality duties in the workplace.

Необхідність реформування системи вищої освіти як у Європейських країнах, так і в Україні зумовила потребу у дослідженні провідного досвіду освітніх практик закладів вищої освіти. Німецька освіта вважається однією з кращих взірців високоякісної сучасної освіти, практику якої наслідує весь світ.Розвиток німецької освіти характеризується переходом до подвійної системи навчання, що успішно застосовується в країні вже більше двадцяти років. І, відповідно, як результат, Німеччина показала високі результати та професійні досягнення студентів, а також один із найнижчих рівнів безробіття молоді. Більше того, увага до німецької освіти зростає через успішне поєднання навчання, практики та підтримки молоді в особистісному та сімейному становленні. Тому вивчення передового досвіду Німеччини у сфері впровадження дуальної освіти є важливим елементом вдосконалення системи української та загальноєвропейської освіти. Досвід Німеччини в організації дуальної системи освіти показує, що для розробки професійних стандартів та навчальних професійних програм потрібен новий дидактичний підхід визначення структури професійного профілю.Порівнявши системи дуального і традиційного навчання, ми схиляємось до твердження, що переваги дуального навчання очевидні: 1) навчання максимально наближене до запитів виробництва; 2) високий відсоток працевлаштування; 3) збільшення різноманітності освітніх програм; 4) більш різнобічний професійний розвиток студента; 5) стимулювання бізнесу у інвестування професійної освіти; 6) виконанню наукових досліджень сприяє можливість використання сучасного виробничого обладнання безпосередньо на виробництві; 7) у моделі дуальної системи навчання є можливість впливати на особистість спеціаліста, формування необхідних якостей працівника; 8) дуальна система навчання як технологія підвищує мотивацію та потреби для отримання знань, необхідних для професійної діяльності, у зв'язку з тим, що якість набутих знань дозволить якісно виконати службові обов'язки на робочому місці.
ОСОБЛИВОСТІ ДУАЛЬНОЇ ОСВІТИ НІМЕЧЧИНИ ЯК ВАЖЛИВОГО ЕЛЕМЕНТУ ПРОФЕСІЙНОЇ ПІДГОТОВКИ ФАХІВЦІВ